Serum sodium alterations in SARS CoV-2 (COVID-19) infection: impact on patient outcome. Issue 1 (28th May 2021) - Berni, Andrea; Malandrino, Danilo; Corona, Giovanni; Maggi, Mario; Parenti, Gabriele; Fibbi, Benedetta; Poggesi, Loredana; Bartoloni, Alessandro; Lavorini, Federico; Fanelli, Andrea; Scocchera, Giulia; Nozzoli, Carlo; et al.
Abstract : Objective: Hyponatremia is the most common electrolyte disorder in hospitalized patients and occurs in about 30% of patients with pneumonia. Hyponatremia has been associated with a worse outcome in several pathologic conditions The main objective of this study was to determine whether serum sodium alterations may be independent predictors of the outcome of hospitalized COVID-19 patients. Design and methods: In this observational study, data from 441 laboratory-confirmed COVID-19 patients admitted to a University Hospital were collected. After excluding 61 patients (no serum sodium at admission available, saline solution infusion before sodium assessment, transfer from another hospital), data from 380 patients were analyzed. Results: 274 (72.1%) patients had normonatremia at admission, 87 (22.9%) patients had hyponatremia and 19 (5%) patients had hypernatremia. We found an inverse correlation between serum sodium and IL-6, whereas a direct correlation between serum sodium and PaO2 /FiO2 ratio was observed. Patients with hyponatremia had a higher prevalence of non-invasive ventilation and ICU transfer than those with normonatremia or hypernatremia. Hyponatremia was an independent predictor of in-hospital mortality (2.7-fold increase vs normonatremia) and each mEq/L of serum sodium reduction was associated with a 14.4% increased risk of death. Conclusions: These results suggest that serum sodium at admission may be considered as an early prognostic marker of disease severity in hospitalized COVID-19 patients.